Adoption of cloud based decision support system for building information modeling software selection - Nursal, Ahmad Taufik; Omar, Mohd Faizal; Mohd Nawi, Mohd Nasrun; Mohammad Asri, Mohammad Azwanie Naim (American Scientific Publishers, 2016)
An increasing numbers of BIM software available in market has led to selection problem among the construction companies. Furthermore, an adoption of BIM is not only involved numerous of attributes, but also required high investment. Thus, selection of appropriate BIM software that fit project need has becoming more apparent. Therefore, this study aims to provide an analytical tool to evaluate and select the most suitable BIM software in fuzzy environment through adoption of contemporary Information Technology (IT) which is Web 2.0. The proposed Web DSS namely topsis4BIM has based on a real construction project in Malaysia.An analytical methodology in topsis4BIM was based on Multi Attributes Decision Making method using fuzzy TOPSIS.The software were evaluated and selected by BIM expert based on seven attributes and five alternatives software. In addition, this study has introduced a new architecture of DSS development through the current Web technology such as Web 2.0 and cloud computing.